Terrestrial-Satellite Communication Networks Transceivers Design and Resource Allocation - Kuang, Linling (Wireless Networks,, 2018)
This book targets major issues in terrestrial-satellite communication networks and presents the solutions. While the terrestrial networks can achieve high-speed data service at low cost, satellite based access is one way to complement terrestrial based networks to ensure ubiquitous, 100% geographic coverage. The coexistence and cooperation between terrestrial and satellite networks are of great potential in future communication networks, and satellite radio access networks has already been considered in the fifth-generation (5G) networks to be supported for phase 2. Therefore, it is important to study the architectures of terrestrial-satellite networks, as well as the possible techniques and challenges. The authors introduce the technique of beamforming in satellite communication systems, which is an efficient transmitting method for multiple access, and they discuss the main challenges as well as prospective applications. The authors introduce possible methods for interference cancelation reception in terrestrial-satellite communication networks when reusing the frequency band between the two networks. Due to the limitation of spectrum resources, spectrum sharing will become one of the important issues in terrestrial-satellite communication networks. The problems of spectrum coexistence between GEO and Terrestrial Systems and between GEO and NEGO systems are also discussed. Finally, taking both the two system into consideration, the resource allocation problem will be more complex due to the coupling between resources and the interference. Based on this, the authors propose several resource allocation schemes in different scenarios of terrestrial-satellite communication networks, which can optimize the capacity performance of the system. The expected audience for this book includes (but not limited to) graduate students, professors, researchers, scientists, practitioners, engineers, industry managers, and government researchers working in the field of satellite communications and networks. The expected audience for this book includes (but not limited to) graduate students, professors, researchers, scientists, practitioners, engineers, industry managers, and government researchers working in the field of satellite communications and networks.